2006
DOI: 10.1038/sj.sc.3101982
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of spasticity with Δ9-tetrahydrocannabinol in persons with spinal cord injury

Abstract: Study design: Open label study to determine drug dose for a randomized double-blind placebocontrolled parallel study. Objectives: To assess the efficacy and side effects of oral D 9 -tetrahydrocannabinol (THC) and rectal THC-hemisuccinate (THC-HS) in SCI patients. Setting: REHAB Basel, Switzerland. Method: Twenty-five patients with SCI were included in this three-phase study with individual dose adjustment, each consisting of 6 weeks. Twenty-two participants received oral THC open label starting with a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 40 publications
1
65
0
Order By: Relevance
“…84,86 Hagenbach et al 70 , showed that THC may have some analgesic properties to help SCI patients with spasticity related pain. Wade et al 87 conducted an RCT of sublingual 2.5 mg THC and/or cannabidiol and found that it significantly reduced pain, muscle spasm, spasticity and sleep difficulties in a group consisting largely of multiple sclerosis patients with neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…84,86 Hagenbach et al 70 , showed that THC may have some analgesic properties to help SCI patients with spasticity related pain. Wade et al 87 conducted an RCT of sublingual 2.5 mg THC and/or cannabidiol and found that it significantly reduced pain, muscle spasm, spasticity and sleep difficulties in a group consisting largely of multiple sclerosis patients with neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…The third phase of the study, involved a double blind randomized control trial which included 13 of the previously mentioned individuals receiving either individual maximum treatment dosage previously determined or a placebo dose. In this phase, Hagenbach et al 70 , found individuals in the treatment group had no significant pain reduction compared to those in the placebo group.…”
Section: Cannabinoids For Sci Painmentioning
confidence: 97%
See 1 more Smart Citation
“…It was concluded that this pharmacological agent may reduce symptoms of spasticity in patients with multiple sclerosis, but that further studies are needed to show a significant effect on objective measurements of spasticity. It was recently demonstrated that a decrease in both the Ashworth scale and the spasticity sum score was observed in patients with SCI that were given THC [65]. Nevertheless, further randomized clinical trials are needed to elucidate the efficacy of this class of drugs as anti-spastic medications.…”
Section: Cannabinoidsmentioning
confidence: 99%
“…1 The authors have highlighted the difficulty in treating spasticity in SCI patients with the currently available medications, making the point for such trials and researches on this subject. The paper outlines the study objectives as to assess the efficacy and side effects of THC in SCI patients.…”
mentioning
confidence: 99%